Fundamental of stomp music case study: far from too late by no noise percussion / Oly Fizly Othman - Othman, Oly Fizly (2010)
Stomp music is music happens that using any stomp teclmique. Stomp music is the art of creating rhythm ffom sound as stomp music is oliginated from Native American. There are also accompaniments of vocal which sing the melody in this style of music. The musical instrument such as string or brass or any melodic instnlluent need to be bought and it's quite expensive and they preferred sang while stomping as an altemative of the musical instruments. Most of people do appreciate Stomp Music as an effort from a musician to experiment sound using daily objects. Some would even look at it only as an entertainment perfonuance for the choreographic elements. However, most people who appreciate stomp music maybe does not know the fundamental essence in shaping or perfOlming stomp music as "real music". In this study, the purpose is to find the fundamental of stomp music and gather the infonnation about the instrumentation. Since lots oftelminology and definition about stomp music, this research is focusing on the influenced by percussion instruments, and the sound that produce by daily objects.